The historical evolution of the cesarean section rate: from an exception in ancient times to a surfeit in present times - Faundes, Anibal (2021)
This nonsystematic review of the literature aimed to describe the changes that have occurred in the practice of cesarean section delivery from ancient times until today and to evaluate the consequences of these changes for the woman and for her newborn child. In ancient times, cesarean section was only performed post mortem or perimortem to preserve the life of the fetus or to separate it from its dead mother. Currently, this method of delivery is widely used not only in accordance with the adequate medical indications, but also to suit the convenience of the pregnant woman and/or her obstetrician. Such conduct, which has led to increasing numbers of elective procedures, may result in negative consequences for the woman and for her baby. This negative impact is contrary to what is expected when cesarean sections are correctly indicated, in which circumstances the procedure plays an important role as a life-saving intervention for the mother and her newborn infant.